PERILAKU AGREGAT MONETER DALAM SISTEM KEUANGAN/PERBANKAN GANDA DI INDONESIA - Achsani, Noer Azam (Journal of Indonesian Economy and Business, 2008)
The main difference between contemporary Islamic monetary system and conventional monetary system is the replacement of interest system with profitand-loss sharing (PLS) system, which both have different behavior in influencing monetary stability. This study aims to analyze demand for money, conventionally and Islamically, in Indonesia and to determine the relationship between money supply in the two system and price level as the goal of monetary policy. Methods used are Vector Auto Regression (VAR) and Vector Error Correction Model (VECM). The results show that PLS return negatively correlated with Islamic demand for money. In Islamic demand for money, the value of correction error is significant, so that there is an adjustment towards its long-term equilibrium. The Islamic demand for money stabilizes quicker to response the shock from other variables compare to that of conventional demand for money. Moreover, there is no cointegration between money supply, conventionally and Islamically, with price level, so that inflation targeting framework of monetary policy implemented by Bank Indonesia need to be reviewed.Kata Kunci : permintaan uang konvensional, permintaan uang Islam, sistem keuangan/perbankan ganda, VAR/VECM